Analysing public service outsourcing: The value of a regulatory perspective. (September 2017) - Cunningham, Ian; James, Philip
This article draws on findings from two longitudinal case studies of voluntary organisations engaged in delivering social care services via purchaser–provider relations with local authorities. The study focuses on changes to contractual relations, employment conditions in provider organisations and service quality. The article argues the influence of the market on these changes can only be adequately comprehended by rooting the analysis in an understanding of the way in which surrounding regulatory frameworks shape its structure and operation. In doing so, it reveals how in an era of shifting market conditions characterised by greater competition and dramatic local authority cuts, a 'soft' regulatory framework offers little support to partnership relations between voluntary organisations and local authorities. Instead, the regulatory environment undermines financial security among voluntary organisations, degrades employment conditions in them and raises concerns regarding their service quality.